Examining the contribution of YouTube and TikTok to elementary students’ public speaking skills - Lelelangan, Herfika; Sari, Harmita; Junaidi, Junaidi; Yang, Chen Ching (Universitas Muhammadiyah Malang, 2026)
The rapid development of digital technology has transformed students’ learning behaviors and increased the use of social media platforms in educational contexts. This study aimed to examine the contribution of YouTube use, TikTok use, listening skills, and practical exercises to elementary school students’ public speaking abilities in digital learning environments. This research employed a quantitative explanatory design using Structural Equation Modeling (SEM). The participants consisted of 120 elementary school students in Bandung, Indonesia, selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using SPSS and AMOS software through Confirmatory Factor Analysis (CFA) and SEM analysis. The findings revealed that all proposed variables positively and significantly contributed to students’ public speaking abilities. Among the variables, practical exercises demonstrated the strongest contribution, followed by TikTok use, YouTube use, and listening skills. The results indicate that audiovisual social media platforms and communication-oriented learning activities can support students’ confidence, fluency, and communication performance in speaking activities. This study contributes to digital learning and communication pedagogy by providing empirical evidence regarding the structural relationships among social media use, listening skills, practical exercises, and public speaking development among elementary school students. The findings also suggest that YouTube and TikTok can be integrated into communication-oriented learning activities to create more engaging and interactive speaking experiences for young learners.